PENGARUH MOTIVASI KESEJAHTERAAN DAN KOMPETENSI GURU TERHADAP KINERJA GURU SMP DI YAYASAN BUNDA HATI KUDUS DAERAH KHUSUS JAKARTA - Irena Irena; Yunus Handoko; Dany Moendiyah Handarini (Smart Education, 2025)
Abstract: This research aims to determine and analyze 1) the partial influence of motivation on teacher performance, 2) the partial influence of welfare on teacher performance, 3) the partial influence of teacher competence on teacher performance, and 4) the simultaneous influence of motivation, well-being and competence on teacher performance.. Teacher performance is an important aspect in creating quality education. The variables of motivation, well-being and competence are considered as the main factors that can influence the quality of teachers' task implementation. This research uses a quantitative approach with a survey method by distributing questionnaires to 34 respondents at the Mother of the Sacred Heart Foundation Middle School teachers in the Special Region of Jakarta using a purposive sampling technique. Data analysis was carried out using multiple linear regression tests to see the partial and simultaneous influence of the independent variable on the dependent variable. The results of the research show 1) motivation does not have a partially significant effect on teacher performance at the Our Lady of the Sacred Heart Foundation for the Special Region of Jakarta, 2) welfare does not have a partially significant effect on the performance of teachers at the Our Lady of the Sacred Heart Foundation for the Special Region of Jakarta, 3) teacher competence has a partially significant effect on teacher performance at the Our Lady of the Sacred Heart Foundation for the Special Region of Jakarta, and 4) simultaneously, the variables of motivation, well-being and teacher competence simultaneously have a significant effect on teacher performance at the Our Lady of the Sacred Heart Foundation for the Special Region of Jakarta.Â Keywords: Motivation, Well-being, Competence, Teacher Performance, Education. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis 1) pengaruh parsial motivasi terhadap kinerja guru, 2) pengaruh parsial kesejahteraan terhadap kinerja guru, 3) pengaruh parsial kompetensi terhadap kinerja guru, dan 4) pengaruh simultan motivasi, kesejahteraan dan kompetensi terhadap kinerja guru. Kinerja guru merupakan aspek penting dalam menciptakan pendidikan yang berkualitas. Variabel motivasi, kesejahteraan, dan kompetensi dinilai sebagai faktor utama yang dapat memengaruhi kualitas pelaksanaan tugas guru. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei melalui penyebaran kuesioner kepada guru-guru SMP Yayasan Bunda Hati Kudus Daerah Khusus Jakarta berjumlah 34 orang responden dengan tehnik purposive sampling. Analisis data dilakukan dengan uji regresi linear berganda untuk melihat pengaruh parsial dan simultan dari variabel independen terhadap variabel dependen. Hasil penelitian menunjukkan 1) motivasi tidak memiliki pengaruh yang signifikan secara parsial terhadap kinerja guru di Yayasan Bunda Hati Kudus Daerah Khusus Jakarta, 2) kesejahteraan tidak berpengaruh yang signifikan secara parsial terhadap kinerja guru di Yayasan Bunda Hati Kudus Daerah Khusus Jakarta, 3) kompetensi guru berpengaruh signifikan secara parsial terhadap kinerja guru di Yayasan Bunda Hati Kudus Daerah Khusus Jakarta, dan 4) secara bersamaan, variabel motivasi, kesejahteraan, dan kompetensi guru secara simultan berpengaruh signifikan terhadap kinerja guru di Yayasan Bunda Hati Kudus Daerah Khusus Jakarta.Â Kata kunci: Motivasi, Kesejahteraan, Kompetensi, Kinerja Guru, Pendidikan